(untitled) (Indian Journal of Child Health, 2022)
Myocarditis is a life-threatening complication of scorpion sting envenomation, and the victims who survive after this injury have normal cardiac function without any residual valvular lesion unlike acute rheumatic fever which causes residual valvular disease by thickening and scarring. We report here a case of a 9-year-old girl who was detected to have valvular heart disease, 2 months after she had scorpion sting envenomation.